Perancangan Buku Ilustrasi Kisah Pasien Ruqyah Syar’iyyah untuk Usia 23-27 Tahun - Diaz Tri Mustikaningrum; Aditya Rahman Yani; Masnuna Masnuna (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2021)
The phenomenon of shamanism is still running in this modern era because some people still believe it. Asking for help from a shaman who deals with things of the occult including the act of shirk or associating partners with Allah. If shirk is done, it is a major sin in Al-Quran. One of ways to avoid being associated with the world of the unseen is by following the method of Ruqyah Syari'yyah. This method has existed since the days of the prophet. Even the Prophet muhammad also never did ruqyah. To overcome this problem, I designed an illustration book that aims to share the experience of people who never do a ruqyah that can be used as a lesson to the target audience because the age of the target audience already entered the complex life such as the experience of the people ruqyah, namely in the field of work, household and so on. The book is accompanied by illustrations that represent each story that look interesting and not boring.